Supervisi Akademik Kepala Sekolah terhadap Manajemen Pembelajaran PAUD - Ittihad Ittihad (LP2M STIT Palapa Nusantara, 2019)
Academic supervision is inseparable from the teacher in conducting learning management. The purpose of this study was to obtain new findings about: 1) Conformity between learning management in Al Urwatul Usqo ECD with Permendikbud 137 of 2014; 2) Causes have not been supported by academic supervision by the Al Urwatul Usqo PAUD school principal. This research is a qualitative study with a type of research, namely a case study. This research was conducted in Al Urwatul Usqo PAUD. The subjects in this study were principals. Data collection techniques used are interviews and documents. Data analysis techniques in this study used qualitative descriptive analysis techniques. Five